Immunohistochemical expression of interleukin 8 in skin biopsies from patients with inflammatory acne vulgaris - El Maged Rabee A; Shoukry Noha S; Abd El All Howayda S; Ayada Mostafa M (BMC, 2007)
Abstract Background This study was conducted to evaluate the immunohistochemical (IHC) expression of interleukin 8 (IL-8) in skin biopsies of inflammatory acne vulgaris (IAV) in an attempt to understand the disease pathogenesis. Materials and methods A total of 58 biopsies, 29 from lesional IAV and 29 normal non lesional sites were immunostained for IL-8. The intensity of staining was evaluated in the epidermis and dermis and was scored as mild, moderate and severe. The expression was correlated with the clinical grade, disease course and histological changes. Results IL-8 immunoreactivity was expressed in lesional IAV compared to non lesional skin biopsies (p < 0.001). Increased expression was significantly associated with epidermal hyperplasia and follicular hyperkeratosis (p < 0.001). In addition, the more pronounced IL-8 expression of the dermal endothelial cells and neutophilic inflammatory infiltrate correlated with dermal angiogenesis and the extent of dermal inflammatory response (p < 0.001). Moreover, increased dermal immunoreactivity paralleled progressive course (p = 0.02) but not the duration of the disease. Conclusion We were able to demonstrate altered immunoreactivity of IL-8 in IAV compared to normal skin. Targeted therapy to block IL-8 production may hold promise in limiting the deleterious effects of IL-8-mediated inflammatory response and angiogenesis.